CRH-R2 signalling modulates feeding and circadian gene expression in hypothalamic mHypoA-2/30 neurons - Alcántara-Alonso, Viridiana; Dallmann, Robert; Lehnert, Hendrik; de Gortari, Patricia; Grammatopoulos, Dimitris K. (Frontiers in Endocrinology, 2023)
The hypothalamic type 2 corticotropin releasing hormone receptor (CRH-R2) plays critical roles in homeostatic regulation, particularly in fine tuning stress recovery. During acute stress, the CRH-R2 ligands CRH and urocortins promote adaptive responses and feeding inhibition. However, in rodent models of chronic stress, over-exposure of hypothalamic CRH-R2 to its cognate agonists is associated with urocortin 2 (Ucn2) resistance; attenuated cAMP-response element binding protein (CREB) phosphorylation and increased food intake. The molecular mechanisms involved in these altered CRH-R2 signalling responses are not well described. In the present study, we used the adult mouse hypothalamus-derived cell line mHypoA-2/30 to investigate CRH-R2 signalling characteristics focusing on gene expression of molecules involved in feeding and circadian regulation given the role of clock genes in metabolic control. We identified functional CRH-R2 receptors expressed in mHypoA-2/30 cells that differentially regulate CREB and AMP-activated protein kinase (AMPK) phosphorylation and downstream expression of the appetite-regulatory genes proopiomelanocortin (Pomc) and neuropeptide Y (Npy) in accordance with an anorexigenic effect. We studied for the first time the effects of Ucn2 on clock genes in native and in a circadian bioluminescence reporter expressing mHypoA-2/30 cells, detecting enhancing effects of Ucn2 on mRNA levels and rhythm amplitude of the circadian regulator Aryl hydrocarbon receptor nuclear translocator-like protein 1 (Bmal1), which could facilitate anorexic responses in the activity circadian phase. These data uncover novel aspects of CRH-R2 hypothalamic signalling that might be important in regulation of circadian feeding during stress responses.